Community Participation in Village Regulation Development in Indonesia (In Law Number 6 of 2014, concerning Villages) - Saputra, Agung Arafat (Yayasan Sinergi Kawula Muda, 2023)
There is an obligation to involve the community in the drafting of village regulations. Therefore, this conceptual article aims to explore the process of formation and community participation in the development of village regulations. The approach used is a statutory one, involving the collection and descriptive analysis of primary and secondary legal materials. The findings indicate, firstly, the stages of village regulation formation start from planning, drafting, discussion, determination, promulgation, to dissemination. Secondly, community participation in the development of village regulations reflects the presence of a democratic political relationship in village governance. Additionally, the intended participation can serve as a platform for discussing and reaching agreements on strategic matters.